2004
DOI: 10.1177/1077559503261181
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability or Resilience to Intergenerational Sexual Abuse: The Role of Maternal Factors

Abstract: This study examined vulnerability or resilience to intergenerational sexual abuse. The sample included 196 African American mothers and their children of which 96 were sexually abused and 100 had no reported incidents of abuse. Four groups were formed based on maternal report of a history of childhood sexual abuse and the child's abuse status: (a) sexually abused mothers of children who were not sexually abused, (b) sexually abused mothers whose child was sexually abused, (c) mothers with no history of sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
17

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 55 publications
2
37
1
17
Order By: Relevance
“…Other researchers have also found that among the strongest predictors of girls' sexual abuse is a history of child sexual abuse in the mother (Faller, 1989;Leifer, Kilbane, & Kalick, 2004;Zuravin, McMillen, Panfilis, & Risly-Curtiss, 1996). Daughters who witness the gender-based subjugation of their mothers may internalize the misogyny that underlies their father's or stepfather's abuse.…”
Section: Discussionmentioning
confidence: 91%
“…Other researchers have also found that among the strongest predictors of girls' sexual abuse is a history of child sexual abuse in the mother (Faller, 1989;Leifer, Kilbane, & Kalick, 2004;Zuravin, McMillen, Panfilis, & Risly-Curtiss, 1996). Daughters who witness the gender-based subjugation of their mothers may internalize the misogyny that underlies their father's or stepfather's abuse.…”
Section: Discussionmentioning
confidence: 91%
“…27 When abused women become mothers, they tend to show poor maternal functioning and difficulty to attach to their own children. 24,27 Apparently, maternal attachment constitutes a major determinant of child development outcomes. 27,[29][30][31] A poor attachment quality may have severe consequences for offspring.…”
Section: Resultsmentioning
confidence: 99%
“…O abuso sexual tem sido considerado um problema de saúde pública, com repercussões sociais, emocionais e cognitivas que podem se manifestar no curto e longo prazos (Gonçalves & Ferreira, 2002;Pfeiffer & Salvagni, 2005;Reppold, Pacheco, Bardagi & Hutz, 2002). Alguns estudos têm definido o abuso sexual infantil (ASI) como qualquer toque genital ou comportamento sexual forçado ou imposto, por meio de ameaça ou força física, a uma criança ou adolescente, no qual o perpetrador tenha pelo menos cinco anos a mais do que a vítima (Alexander, Teti & Anderson, 2000;Leifer, Kilbane & Kalick, 2004). Apresenta-se sob forma de práticas eróticas e sexuais impostas à criança ou ao adolescente pela violência física, ameaças ou indução de sua vontade, e pode variar desde atos em que não se produz o contato sexual (voyerismo, exibicionismo, produção de fotos, pornografia) até diferentes tipos de ações que incluem contato sexual sem ou com penetração (Azevedo & Guerra, 1989; SBP/Claves/ ENSP/Fiocruz/SEDH/MJ, 2001).…”
unclassified